Endogenous security architecture of Ethernet switch based on mimic defense - Ke SONE; Qinrang LIU; Shuai WEI; Wenjian ZHANG; Libo TAN (Tongxin xuebao)
Aiming at the unknown vulnerabilities and unknown backdoor security threats faced by Ethernet switches,a switch endogenous security architecture based on mimicry defense theory was proposed.The theoretical basis,construction mode and security mechanism of the architecture ware introduced,the algorithm strategy and security improvement effect of TAMA algorithm were proposed and analyzed,a prototype of mimic switch was designed and implemented,and the security tests of white box stuffing and attack chain were carried out.Theoretical analysis and test results show that the architecture has good unknown vulnerabilities and unknown backdoor defense capabilities in various attack scenarios.